Condições higiênico-sanitárias de agroindústrias familiares de produtos de panificação de Francisco Beltrão, PR - Massarollo, Marina Daros (2014)
The family agribusinesses, that have emerged to take advantage of the surplus that is not go to the market, together and to cope with this unfavorable prices, differ from traditional agribusinesses by exclusively using hand labor in family production and processing products adding value to the final product. With the increase in foodborne diseases in recent years, due to factors such as population growth, vulnerable or exposed groups, unplanned urbanization and food production scale, aimed to evaluate the sanitary conditions of eight agro baking from Francisco Beltrão who provide their products for school lunches, as well as evaluating the sanitary quality of products through microbiological analysis. Parallel to this, were applied a good practices training of manufacturing and elaborated good practices manual for each of the agribusinesses. The evaluation of agribusinesses sanitary-hygienic conditions enabled visualization of changes that could be made, which were suggested in an action plan and many of them worked by agribusinesses, increasing the percentage of compliances items in the check list verification. Simultaneously, the results of microbiological analysis improved when compared to the assessment of the first and second batch. This was possible through the good practices training of manufacturing ministered to producers. The implementation of good manufacturing practices in agribusinesses was efficient, because it improves the microbiological quality of products offered to school meals.